The expertise economy how the smartest companies use learning to engage, compete, and succeed - Kelly Palmer and David Blake (2018 Nicholas Brealey Publishing)
Keeping people's skills in sync with fast-changing markets is the biggest challenge of our time.
Includes index.
Keywords: Employees--Training of